AB0364 Remarkable international variability in reasons for non-participation in the gloria trial. (12th June 2018) - Hartman, L.; Bos, R.; Buttgereit, F.; Güler-Yuksel, M.; Ionescu, R.; Kok, M.; Lems, W.; Micaelo, M.; Opris-Belinski, D.; Pusztai, A.; Santos, E.; da Silva, J.; et al.
Abstract : Background: GLORIA is an ongoing large pragmatic trial that examines harm, benefit and costs of low-dose glucocorticoids added to the standard treatment of RA patients of 65 years or older. The eligibility criteria are non-restrictive: RA, age ≥65 years, disease activity score (DAS28) of ≥2.6, and no current glucocorticoid treatment. Patients with comorbidity are expressly included, and the impact of trial procedures on normal care is minimal. Nevertheless, inclusion proves to be challenging. We have prospectively sampled all the reasons for ineligibility across a number of centres in different countries participating in the GLORIA trial. Methods: Rheumatologists from 8 centres in Germany, Hungary, The Netherlands, Portugal and Romania screened the patient list of at least two full clinic days. For each patient, the eligibility and all possible reasons of exclusion were recorded. Results: In total, 385 patients were screened. Of these patients, 15 (4%) were eligible to participate in the GLORIA trial. In Germany, Romania and Portugal (Lisbon) none of the screened patients proved eligible. The most common reasons for ineligibility were inactive disease and age (both 58%) (table 1). Current glucocorticoid use was reported in 28%, 5% had a temporary reason (i.e. recent switch of therapy or glucocorticoid use), and 51% had more than one reason for ineligibility. We found remarkable differences between the sites in the distribution of the main reasons for ineligibility (table 1). Of the eligible patients, 1 was already participating, 3 were included after this screening, and 2 were currently considering participation; 9 declined participation (most common reasons: fear of glucocorticoids, not interested to participate, preference for GC injections or declining additional therapy). Conclusions: In this prospective study, we found remarkable differences between countries in reasons for non-participation in our ongoing GLORIA trial. The willingness of eligible patients to participate was low in this elderly population, despite the pragmatic design. Earlier studies also showed that it is challenging to include elderly patients in a clinical trial. 1 2 Pre-screening of patients in potential sites can provide important information on the potential to recruit patients in a trial, but the actual willingness of patients to participate remains hard to predict. References: [1] Calamia M, et al. I'd Do Anything for Research, But I Won't Do That: Interest in Pharmacological Interventions in Older Adults Enrolled in a Longitudinal Aging Study. PLoS One2016;11:e0159664. [2] Denson AC, et al. Participation of the elderly population in clinical trials: barriers and solutions. Cancer Control2014;21:209–14. Acknowledgements: This project has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No 6 34 886. Disclosure of Interest: None declared